A multi-tone ultraviolet photochromic coating material and its synthesis process
By using a combination of a variety of organic photochromic agents and nano-scale titanium oxide particles, the problem of limited color variation range and poor stability of existing photochromic materials is solved, and significant color changes and light resistance are achieved, which is suitable for diverse applications.
Patent Information
- Application Number
- CN202411444940.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The color range of existing photochromic materials is limited and have poor stability. Especially under ultraviolet irradiation, color degradation is prone to occur, affecting service life and application effect.
A combination of a variety of organic photochromic agents, including 3,4-dihydro-2H-1-benzopyran and 2H-benzopyran-2-one, is used to combine nano-scale titanium oxide particles to form a composite structure, improving stability and multiple photochromic effects.
Significant color changes are achieved and the light resistance and stability of the material is improved, the service life is extended, and suitable for use in outdoor or in extreme climates.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating materials, in particular to a multi-tone ultraviolet photochromic coating material and a synthesis process thereof. Background Art
[0002] With the widespread development of optical applications, the demand for photochromic materials in the fields of UV protection, spectrum adjustment, decoration, etc. is increasing. Existing photochromic coatings mostly use a single photochromic agent, which limits the range of color changes and cannot meet the diverse application needs. In addition, many existing materials have poor stability under light conditions and are prone to color degradation or performance degradation, affecting their actual service life and effect;
[0003] First, existing photochromic materials usually rely on a single type of photochromic agent, resulting in limited color changes. Many products can only show limited color changes under specific lighting conditions.
[0004] Second, existing organic photochromic agents often show poor stability under ultraviolet radiation. Long-term exposure to sunlight will lead to the weakening or complete loss of the photochromic effect, which not only reduces the service life of the material, but also affects its application effect in outdoor or high ultraviolet environments;
[0005] 3. Existing composite materials of organic and inorganic photochromic agents often have poor stability of photochromic properties and mechanical properties due to insufficient interaction. For example, organic components may decompose in high temperature or humid environments, while insufficient uniform dispersion of inorganic components will affect the photochromic effect.
[0006] Based on this, a multi-tone ultraviolet photochromic coating material and a synthesis process thereof are needed. Summary of the invention
[0007] To achieve the above object, the present invention provides the following solution: a multi-tone ultraviolet photochromic coating material, comprising, by mass percentage:
[0008] Organic photochromic agent 30-60%: composed of benzopyran compounds, including 3,4-dihydro-2H-1-benzopyran and 2H-benzopyran-2-one. The two compounds change color due to changes in molecular structure under light conditions;
[0009] Inorganic photochromic agent 20-50%: composed of nano-sized titanium oxide particles, which are combined with the organic photochromic agent as an inorganic component to form a composite structure, so that the nano-sized titanium oxide particles exist in the coating in a uniformly dispersed form;
[0010] Polymer matrix 10-30%: Contains one or more combinations of polyurethane, acrylic or epoxy resins, with the polymer as the matrix material, tightly combined with organic and inorganic components;
[0011] Additives 0.1-5%.
[0012] Further preferably, the additives include 0.5-2% antioxidant, 1-3% ultraviolet absorber and 0.1-1% dispersant by mass percentage, and the additives interact with the organic photochromic agent, the inorganic photochromic agent and the polymer substrate to improve the dispersion and uniformity of the material.
[0013] Further preferably, the organic photochromic agent further comprises 1-5% of a functional additive, wherein the functional additive is selected from 1-2% of a light stabilizer, 0.5-1.5% of a tackifier or 0.1-0.5% of an antibacterial agent, and the functional additive is combined with the organic photochromic agent to improve the adhesion and weather resistance of the material.
[0014] In addition, the present invention also provides a synthesis process of a multi-tone ultraviolet photochromic coating material, comprising the following synthesis steps:
[0015] Step 1, wherein 3,4-dihydro-2H-1-benzopyran accounts for 40% of the total organic photochromic agent, that is, 12-24% of the total mass of the coating material, and 2H-benzopyran-2-one accounts for 60%, that is, 18-36% of the total mass of the coating material. The purity of these two compounds is not less than 95% to ensure that the molecular structure can effectively change under light conditions to achieve the desired color change. At the same time, prepare nano-scale titanium oxide particles, which account for 20-50% of the total formula, and the particle size needs to be controlled at 10-50 nanometers. Then, select a polymer substrate with a ratio of 10-30%, use a single or multiple combinations of polyurethane, acrylic or epoxy resin, and finally, prepare additives, including 0.5-2% antioxidant, 1-3% ultraviolet absorber and 0.1-1% dispersant;
[0016] Step 2: In a stirrer, the required proportion of the organic photochromic agent is mixed with the polymer substrate, and the stirring speed is set to 300-500 rpm for 30 minutes to make the preliminary mixture uniform. Subsequently, the nano-sized titanium oxide particles are gradually added and the stirring is continued. The total stirring time reaches 60 minutes to ensure that it is evenly distributed in the coating material. After adding the auxiliary agent, the stirring is continued until the total time of the entire stirring process reaches 90 minutes, so that the auxiliary agent fully interacts with the organic and inorganic components.
[0017] Step 3: After fully mixing, gradually add solvent as needed to make the viscosity of the mixture reach 500-1000cP for spraying. After stirring evenly, let it stand for 10 minutes to observe the bubbles in the mixture to ensure that there are no obvious bubbles.
[0018] Step 4: Spray the coating material evenly on the surface to be treated. The coating thickness needs to be controlled within 50-100 microns. This thickness range ensures the best performance of the photochromic performance. During the coating process, the ambient temperature is maintained at 20-25°C and the humidity is controlled at 30-50%.
[0019] Step 5: After coating, place the coating in a well-ventilated dry environment to dry naturally for 24 hours. Then, place the coating material in an oven preheated to 60-80°C for curing, and the curing time is set to 1-2 hours.
[0020] Step 6: Perform photochromic performance, adhesion test, weather resistance test and UV resistance test on the cured coating.
[0021] Further preferably, in the step 3, the gradually added solvent includes alcohols and ketones;
[0022] The alcohol solvent is isopropanol or ethanol;
[0023] Acetone is selected as the ketone solvent;
[0024] Adding solvent is used to adjust the viscosity of the coating material. According to the required viscosity and formula, add the solvent gradually and stir well.
[0025] Further preferably, in the step 4, the coating material is placed in a vacuum environment for degassing treatment, the vacuum degree is -0.1 to -0.2 MPa, and the treatment time is 10-20 minutes to remove bubbles generated during the mixing process.
[0026] Further preferably, in the step five, the mixed coating material is subjected to high shear mixing, that is, the mixture is stirred at a high shear rate of 2000-5000RPM for 15-30 minutes to enhance the interaction between the components.
[0027] Further preferably, in step six, the treated coating material is dried by spray drying, the spray temperature is set to 120-160° C., and the drying time is 1-3 hours to quickly remove excess solvent.
[0028] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:
[0029] 1. The present invention uses a combination of multiple organic photochromic agents, including 3,4-dihydro-2H-1-benzopyran, so that it can quickly undergo photochromic reactions under ultraviolet light and show significant color changes. Its unique conjugated system can effectively absorb light of a specific wavelength, thereby triggering electron transfer within the molecule, resulting in a color change. Compared with 3,4-dihydro-2H-1-benzopyran, 2H-benzopyran-2-one exhibits higher stability and lower photolysis rate under ultraviolet light, allowing it to maintain its photochromic effect under long-term illumination conditions, thereby extending the service life of the coating. By combining the characteristics of the two compounds, the coating can achieve multiple photochromic changes;
[0030] Second, the present invention combines nano-scale titanium oxide particles to improve the light resistance and stability of the coating. Titanium oxide can not only effectively absorb harmful ultraviolet rays, but also slow down the photolysis process of organic photochromic agents, reduce the weakening of photochromic effects, and ensure that the coating can still maintain its photochromic properties when exposed to strong ultraviolet rays for a long time, greatly extending the service life of the material. In addition, the enhanced light resistance makes the coating material more suitable for use in outdoor environments and extreme climate conditions;
[0031] 3. The present invention achieves good interaction between organic and inorganic photochromic agents, and adopts nano-scale titanium oxide particles to effectively improve the stability of organic components in high temperature and humid environments, avoid decomposition, and enhance the durability of the material. In addition, the stability of the photochromic performance is ensured by the uniform dispersion of titanium oxide, avoiding performance fluctuations caused by uneven dispersion. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 The synthetic process flow chart of the present invention is shown in FIG. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0036] Example 1
[0037] like Figure 1 As shown, a multi-tone ultraviolet photochromic coating material in this embodiment includes, by mass percentage: 40% of an organic photochromic agent, which is composed of benzopyran compounds, wherein 3,4-dihydro-2H-1-benzopyran accounts for 50% (i.e. 20%) of the total organic photochromic agent, and 2H-benzopyran-2-one accounts for 50% (i.e. 20%), and both undergo molecular structural changes under light conditions to change color, thereby achieving a multi-tone effect;
[0038] 30% inorganic photochromic agent, composed of nano-scale titanium oxide particles, forms a composite structure with the organic photochromic agent, so that the nano-scale titanium oxide particles are evenly dispersed in the coating, improving the stability and durability of the photochromic agent;
[0039] 20% polymer matrix, including a combination of polyurethane and epoxy resin, wherein polyurethane accounts for 60% of the total polymer matrix and epoxy resin accounts for 40% of the total polymer matrix, which acts as a matrix material to closely combine with organic and inorganic components to enhance the mechanical strength and chemical resistance of the coating;
[0040] Additives: 5%, of which antioxidants account for 1%, UV absorbers account for 3%, and dispersants account for 1%. Additives interact with organic photochromic agents, inorganic photochromic agents, and polymer substrates to improve the dispersion and uniformity of materials and enhance the overall performance of the coating;
[0041] In addition, the organic photochromic agent further includes a functional additive selected from 5% of a light stabilizer to improve the adhesion, weather resistance and antibacterial properties of the material, thereby extending the service life of the coating and increasing its application range;
[0042] In addition, the present invention also provides a synthesis process of a multi-tone ultraviolet photochromic coating material, comprising the following synthesis steps:
[0043] Step 1: Prepare 3,4-dihydro-2H-1-benzopyran and 2H-benzopyran-2-one, mix them in proportion to ensure that the total amount is 40% and the purity is not less than 95%; prepare nano-sized titanium oxide particles, which account for 30% of the formula and the particle size is controlled at 20 nanometers; select a combination of polyurethane and epoxy resin, with the polymer base material accounting for 20%; the configuration of the additives is 1% antioxidant, 3% ultraviolet absorber and 1% dispersant;
[0044] Step 2: In a blender, 40% of the organic photochromic agent was mixed with 20% of the polymer substrate at a stirring speed of 400 rpm for 30 minutes to ensure that the initial mixture was uniform; then 30% of the nano-sized titanium oxide particles were gradually added and stirred for 60 minutes to ensure that they were evenly distributed; after adding the additive, the stirring time was extended to 90 minutes to fully promote the interaction of the components;
[0045] Step 3: After sufficient mixing, gradually add an appropriate amount of solvent to make the mixture viscosity reach 700cP; after stirring evenly, let it stand for 10 minutes and check the bubbles in the mixture to ensure that there are no obvious bubbles;
[0046] Step 4: Spray the coating material evenly on the surface to be treated, and the coating thickness is controlled at 80 microns; during this process, the coating material is placed in a vacuum environment for degassing, the vacuum degree is set to -0.15MPa, the treatment time is 15 minutes, the ambient temperature is maintained at 22°C, and the humidity is controlled at 40%;
[0047] Step 5: After coating, the coating is placed in a well-ventilated dry environment to dry naturally for 24 hours; then, the coating material is placed in an oven preheated to 70°C for curing, and the curing time is set to 1.5 hours; in this step, the mixed coating material is subjected to high shear mixing with a shear rate of 3000RPM and a mixing time of 20 minutes to enhance the interaction between the components;
[0048] Example 2
[0049] The difference from Example 1 is that it comprises, by mass percentage:
[0050] Organic photochromic agent: 35%, composed of benzopyran compounds, of which 3,4-dihydro-2H-1-benzopyran accounts for 60% (i.e. 21%) of the total organic photochromic agent, and 2H-benzopyran-2-one accounts for 40% (i.e. 14%), and the purity of the two compounds is not less than 95%;
[0051] Inorganic photochromic agent: 25%, composed of nano-sized titanium oxide particles, with particle size controlled at 15 nanometers to ensure uniform distribution;
[0052] Polymer matrix: 30%, including a combination of acrylic and polyurethane, with acrylic accounting for 70% of the total polymer matrix and polyurethane accounting for 30% of the total polymer matrix, enhancing the mechanical strength and chemical resistance of the coating;
[0053] Additives: 5%, of which antioxidants account for 1.5%, UV absorbers account for 2%, and dispersants account for 1.5%;
[0054] Functional additives: viscosity enhancer, the proportion is 5%.
[0055] Synthesis process steps:
[0056] Step 1: Prepare 3,4-dihydro-2H-1-benzopyran and 2H-benzopyran-2-one, mix them in proportion to ensure that the total amount is 35%, and the purity is not less than 95%; prepare nano-sized titanium oxide particles, which account for 25% of the formula, and the particle size is controlled at 15 nanometers; select a combination of acrylic acid and polyurethane, and the polymer base material accounts for 30%; the auxiliary agent is configured as 1.5% antioxidant, 2% ultraviolet absorber and 1.5% dispersant;
[0057] Step 2: In a blender, 35% of the organic photochromic agent was mixed with 30% of the polymer substrate at a stirring speed of 350 rpm for 30 minutes to ensure that the initial mixture was uniform; then 25% of the nano-sized titanium oxide particles were gradually added and stirred for 60 minutes to ensure that they were evenly distributed; after adding the additive, the stirring time was extended to 90 minutes;
[0058] Step 3: After sufficient mixing, gradually add an appropriate amount of solvent to make the mixture viscosity reach 800cP; after stirring evenly, let it stand for 10 minutes and check the bubbles in the mixture to ensure that there are no obvious bubbles;
[0059] Step 4: Spray the coating material evenly on the surface to be treated, and the coating thickness is controlled at 70 microns; place the coating material in a vacuum environment for degassing, the vacuum degree is set to -0.1MPa, the treatment time is 10 minutes, the ambient temperature is maintained at 25°C, and the humidity is controlled at 35%;
[0060] Step 5: After coating, place the coating in a well-ventilated dry environment to dry naturally for 24 hours; then, place the coating material in an oven preheated to 75°C for curing, and the curing time is set to 1 hour; in this step, the mixed coating material is subjected to high shear mixing, with a shear rate of 2500RPM and a mixing time of 25 minutes.
[0061] Example 3
[0062] Different from Examples 1 and 2, it comprises, by mass percentage:
[0063] Organic photochromic agent: 45%, composed of benzopyran compounds, of which 3,4-dihydro-2H-1-benzopyran accounts for 40% (i.e. 18%) of the total organic photochromic agent, and 2H-benzopyran-2-one accounts for 60% (i.e. 27%), and the purity of the two compounds is not less than 95%;
[0064] Inorganic photochromic agent: 20%, composed of nano-sized titanium oxide particles, with particle size controlled at 30 nanometers;
[0065] Polymer matrix: 25%, including a combination of epoxy resin and acrylic, with epoxy resin accounting for 60% of the total polymer matrix and acrylic acid accounting for 40% of the total polymer matrix, enhancing the mechanical strength and chemical resistance of the coating;
[0066] Additives: 5%, of which antioxidant accounts for 1%, UV absorber accounts for 3%, and dispersant accounts for 1%;
[0067] Functional additives: antibacterial agent, the proportion is 5%.
[0068] Synthesis process steps:
[0069] Step 1: Prepare 3,4-dihydro-2H-1-benzopyran and 2H-benzopyran-2-one, mix them in proportion to ensure that the total amount is 45% and the purity is not less than 95%; prepare nano-sized titanium oxide particles, which account for 20% of the formula and the particle size is controlled at 30 nanometers; select a combination of epoxy resin and acrylic acid, with the polymer substrate accounting for 25%; the auxiliary agent is configured as 1% antioxidant, 3% ultraviolet absorber and 1% dispersant;
[0070] Step 2: In a blender, 45% of the organic photochromic agent was mixed with 25% of the polymer substrate at a stirring speed of 400 rpm for 30 minutes to ensure that the initial mixture was uniform; then 20% of the nano-sized titanium oxide particles were gradually added and stirring was continued for 60 minutes; after adding the additive, the stirring time was extended to 90 minutes;
[0071] Step 3: After sufficient mixing, gradually add an appropriate amount of solvent to make the mixture viscosity reach 600cP; after stirring evenly, let it stand for 10 minutes and check the bubbles in the mixture to ensure that there are no obvious bubbles;
[0072] Step 4: Spray the coating material evenly on the surface to be treated, and the coating thickness is controlled at 60 microns; place the coating material in a vacuum environment for degassing, the vacuum degree is set to -0.12MPa, the treatment time is 15 minutes, the ambient temperature is maintained at 23°C, and the humidity is controlled at 32%;
[0073] Step 5: After coating, place the coating in a well-ventilated dry environment to dry naturally for 24 hours; then, place the coating material in an oven preheated to 65°C for curing, and the curing time is set to 1.5 hours; in this step, the mixed coating material is subjected to high shear mixing, with a shear rate of 2800RPM and a mixing time of 20 minutes.
[0074] Example 4
[0075] Different from Examples 1, 2 and 3, it comprises, by mass percentage:
[0076] Organic photochromic agent: 50%, composed of benzopyran compounds, of which 3,4-dihydro-2H-1-benzopyran accounts for 70% (i.e. 35%) of the total organic photochromic agent, and 2H-benzopyran-2-one accounts for 30% (i.e. 15%), and the purity of the two compounds is not less than 95%;
[0077] Inorganic photochromic agent: 15%, composed of nano-sized titanium oxide particles with a particle size controlled at 25 nanometers;
[0078] Polymer matrix: 30%, including a combination of polyurethane and acrylic, with polyurethane accounting for 50% of the total polymer matrix and acrylic accounting for 50% of the total polymer matrix;
[0079] Additives: 5%, of which antioxidants account for 2%, UV absorbers account for 2%, and dispersants account for 1%;
[0080] Functional additives: light stabilizer, the proportion is 5%.
[0081] Synthesis process steps:
[0082] Step 1: Prepare 3,4-dihydro-2H-1-benzopyran and 2H-benzopyran-2-one, mix them in proportion to ensure that the total amount is 50%, and the purity is not less than 95%; prepare nano-sized titanium oxide particles, which account for 15% of the formula, and the particle size is controlled at 25 nanometers; select a combination of polyurethane and acrylic acid, and the polymer base material accounts for 30%; the auxiliary agent is configured as 2% antioxidant, 2% ultraviolet absorber and 1% dispersant;
[0083] Step 2: In a blender, 50% of the organic photochromic agent was mixed with 30% of the polymer substrate at a stirring speed of 450 rpm for 30 minutes to ensure that the initial mixture was uniform; then 15% of the nano-sized titanium oxide particles were gradually added and stirring was continued for 60 minutes; after adding the additive, the stirring time was extended to 90 minutes;
[0084] Step 3: After sufficient mixing, gradually add an appropriate amount of solvent to make the mixture viscosity reach 900cP; after stirring evenly, let it stand for 10 minutes and check the bubbles in the mixture to ensure that there are no obvious bubbles;
[0085] Step 4: Spray the coating material evenly on the surface to be treated, the coating thickness is controlled at 90 microns, and the coating material is placed in a vacuum environment for degassing treatment, the vacuum degree is set to -0.08MPa, the treatment time is 10 minutes, the ambient temperature is maintained at 20°C, and the humidity is controlled at 30%;
[0086] Step 5: After coating, the coating was placed in a well-ventilated dry environment to dry naturally for 24 hours. Subsequently, the coating material was placed in an oven preheated to 80°C for curing, and the curing time was set to 1 hour. In this step, the mixed coating material was subjected to high shear mixing, with a shear rate of 3200RPM and a mixing time of 15 minutes.
[0087] Example 5
[0088] Different from Examples 1, 2, 3 and 4, it comprises, by mass percentage:
[0089] Organic photochromic agent: 40%, composed of benzopyran compounds, of which 3,4-dihydro-2H-1-benzopyran accounts for 50% (i.e. 20%) of the total organic photochromic agent, and 2H-benzopyran-2-one accounts for 50% (i.e. 20%), and the purity of the two compounds is not less than 95%;
[0090] Inorganic photochromic agent: 30%, composed of nano-sized titanium oxide particles, with particle size controlled at 20 nanometers;
[0091] Polymer matrix: 20%, including a combination of polyurethane and epoxy resin, with polyurethane accounting for 40% of the total polymer matrix and epoxy resin accounting for 60% of the total polymer matrix, enhancing the mechanical strength and chemical resistance of the coating;
[0092] Additives: 5%, of which antioxidant accounts for 1%, UV absorber accounts for 3%, and dispersant accounts for 1%;
[0093] Functional additives: antibacterial agent, the proportion is 5%.
[0094] Synthesis process steps
[0095] Step 1: Prepare 3,4-dihydro-2H-1-benzopyran and 2H-benzopyran-2-one, mix them in proportion to ensure that the total amount is 40% and the purity is not less than 95%; prepare nano-sized titanium oxide particles, which account for 30% of the formula and the particle size is controlled at 20 nanometers; select a combination of polyurethane and epoxy resin, with the polymer base material accounting for 20%; the configuration of the additives is 1% antioxidant, 3% ultraviolet absorber and 1% dispersant;
[0096] Step 2: In a blender, 40% of the organic photochromic agent was mixed with 20% of the polymer substrate at a stirring speed of 400 rpm for 30 minutes to ensure that the initial mixture was uniform; then 30% of the nano-sized titanium oxide particles were gradually added and stirred for 60 minutes to ensure that they were evenly distributed; after adding the additive, the stirring time was extended to 90 minutes;
[0097] Step 3: After sufficient mixing, gradually add an appropriate amount of solvent to make the mixture viscosity reach 700cP; after stirring evenly, let it stand for 10 minutes and check the bubbles in the mixture to ensure that there are no obvious bubbles;
[0098] Step 4: Spray the coating material evenly on the surface to be treated, and the coating thickness is controlled at 80 microns; place the coating material in a vacuum environment for degassing, the vacuum degree is set to -0; 15MPa, the treatment time is 15 minutes, the ambient temperature is maintained at 22°C, and the humidity is controlled at 40%;
[0099] Step 5: After coating, place the coating in a well-ventilated dry environment to dry naturally for 24 hours; then, place the coating material in an oven preheated to 70°C for curing, and the curing time is set to 1.5 hours; in this step, the mixed coating material is subjected to high shear mixing, with a shear rate of 3000RPM and a mixing time of 20 minutes.
[0100] Sources and brands of raw materials used in this example:
[0101] 3,4-Dihydro-2H-1-benzopyran, the CAS number of the compound is 493-08-3; source: Alfa Aesar, brand name: Chroman;
[0102] 2H-Benzopyran-2-one, CAS number of the compound: 91-64-5; source: Alfa Aesar, brand name: Coumarin;
[0103] Nano-sized titanium oxide particles: Source: Evonik Industries; Brand: AEROSIL T805; CAS number: 13463-67-7; AEROSIL T805 nano-sized titanium dioxide, used for light stabilization and enhanced mechanical properties;
[0104] Polyurethane: Source: BASF; Brand: Elastollan 1185A; CAS No.: 9009-54-5; Elastollan is a polyurethane series product of BASF, used for high-performance coatings;
[0105] Acrylic acid: Source: BASF; Brand: Acronal 290 D; CAS No.: 79-10-7; Acronal 290 D is an acrylic acid-based polymer emulsion used for coatings;
[0106] Epoxy resin: Source: Huntsman; Brand: Araldite GY 6010; CAS number: 25068-38-6; Araldite GY 6010 is a bisphenol A type epoxy resin used in coatings and adhesives;
[0107] Antioxidant: Source: BASF; Brand: Irganox 1010; CAS No.: 6683-19-8;
[0108] UV absorber: Source: BASF; Brand: TINUVIN 400; CAS No.: 153519-44-9;
[0109] Dispersant: Source: Stepan Company; Brand: STEPANOL NP-9; CAS No.: 36290-04-7;
[0110] Light stabilizer: Source: BASF; Brand: TINUVIN 123; CAS No.: 129757-67-1;
[0111] Tackifier: Eastman AQ 1350; Source: Eastman Chemical Company; CAS No.: 25852-37-3;
[0112] Antimicrobial agent: Source: Microban International; Brand: SilverShield series; CAS number: 7440-22-4; SilverShield is a nanosilver-based antimicrobial agent used in coatings to provide an antimicrobial effect.
[0113] Photochromic performance test example:
[0114] The cured coating is tested for photochromic properties, adhesion, weather resistance and UV resistance;
[0115] 1. Photochromic performance test: Evaluate the color change ability of multi-tone UV photochromic coating materials under UV light to determine their photochromic performance:
[0116] Test equipment: UV light source (wavelength 365nm), spectrophotometer and photometer for color measurement (using colorimeter);
[0117] step:
[0118] S1. Sample preparation: Cut the coating samples of the same size (10 cm x 10 cm) from each example;
[0119] S2. Initial measurement: Use a spectrophotometer to measure the initial absorbance of the sample and record the absorbance values at wavelengths of 400nm, 500nm and 600nm;
[0120] S3, UV irradiation: Place the sample under a UV light source, set the irradiation time to 2 hours, and record the absorbance change of the sample every 30 minutes;
[0121] S4. Subsequent measurement: After the irradiation is completed, the absorbance of the sample is measured immediately and its absorbance value at the same wavelength is recorded;
[0122] S5. Data analysis: Compare the absorbance values before and after irradiation and calculate the absorbance change.
[0123] Table 1 - Photochromic performance test results
[0124] Example Initial absorbance (400nm) Absorbance (after irradiation, 400nm) Absorbance change (400nm) Initial absorbance (600nm) Absorbance (after irradiation, 600nm) Absorbance change (600nm) 1 0.10 0.85 0.75 0.05 0.20 0.15 2 0.12 0.80 0.68 0.06 0.15 0.09 3 0.09 0.78 0.69 0.04 0.18 0.14 4 0.11 0.82 0.71 0.05 0.17 0.12 5 0.08 0.88 0.80 0.03 0.22 0.19
[0125] Absorbance change: The absorbance change of Example 5 is 0.80, which is greater than the absorbance change of Example 1, which is 0.75. Therefore, Example 5 exhibits the best photochromic effect under 400nm ultraviolet light. Although the absorbance change of Example 1 is close to that of Example 5, showing significant color changing ability, its absorbance change is slightly lower than that of Example 5, so its photochromic effect is slightly inferior to that of Example 5;
[0126] Color change: All examples showed obvious color change after UV irradiation, and the change was more significant at 400nm wavelength, indicating that the material has excellent photochromic performance at this wavelength;
[0127] Conclusion: According to the test results, all examples exhibited good photochromic properties, especially Example 1 and Example 5 showed significant color changes under ultraviolet light irradiation, and the absorbance change values showed that they were suitable for coating applications requiring photochromic properties.
[0128] Adhesion test example:
[0129] Verify the adhesion of multi-tone UV photochromic coating materials on optometry-related substrates to ensure their stability and durability in practical applications;
[0130] Test materials: coating samples of Examples 1 to 5;
[0131] Test substrates: ophthalmic lenses, optical coatings, optical films;
[0132] The test method uses a tape peeling test, and the specific steps are as follows:
[0133] S1. Sample preparation: Spray each coating material onto ophthalmic lenses, optical coatings and optical films with a coating thickness of 50-100 microns. Wait for 24 hours after curing to ensure complete drying.
[0134] S2. Tape application: Use standard tape to stick a 10cm long tape on the coating surface, making sure there are no bubbles or wrinkles;
[0135] S3, peeling test: 24 hours after the tape was pasted, the tape was peeled off quickly at a speed of about 30 cm per minute, and the adhesion performance during the peeling process was recorded;
[0136] S4. Evaluation standard: According to ASTM D3359 standard, observe the peeled coating and evaluate the adhesion level:
[0137] Level 5: No peeling;
[0138] Level 4: Minor peeling;
[0139] Level 3: Moderate peeling;
[0140] Level 2: Extensive peeling;
[0141] Level 1: Complete stripping;
[0142] Table 2-Adhesion test results
[0143] Example Substrate Adhesion grade Remark 1 Optical lenses 5 No peeling 1 Optical coating 4 Small amount of peeling 1 Optical Film 3 Medium peeling 2 Optical lenses 4 Small amount of peeling 2 Optical coating 5 No peeling 2 Optical Film 4 Small amount of peeling 3 Optical lenses 5 No peeling 3 Optical coating 3 Medium peeling 3 Optical Film 4 Small amount of peeling 4 Optical lenses 4 Small amount of peeling 4 Optical coating 5 No peeling 4 Optical Film 3 Medium peeling 5 Optical lenses 5 No peeling 5 Optical coating 4 Small amount of peeling 5 Optical Film 5 No peeling
[0144] Based on the adhesion test results of Examples 1 to 5, the following conclusions were drawn:
[0145] Adhesion performance: the adhesion level of most coating samples on the ophthalmic optical lens and the optical coating was 4 or 5, showing good adhesion performance. Among them, the adhesion of Example 1 and Example 3 on the ophthalmic optical lens reached the highest level of 5, indicating that the bonding force between them and the substrate was extremely strong and suitable for long-term use;
[0146] Optical film performance: The adhesion test results of optical films are slightly lower, generally at level 3 or 4. When using optical films as substrates, it is necessary to optimize the coating formulation or perform appropriate surface treatment before application to improve adhesion;
[0147] Weathering test example:
[0148] Evaluate the weatherability of the developed multi-tone UV photochromic coating material under different climatic conditions to determine its stability and reliability for long-term use;
[0149] Test method: Use an artificial climate accelerated test chamber to simulate weather resistance testing on coating samples. The test cycle is set to 300 hours and is divided into three parts: ultraviolet radiation, temperature change and humidity;
[0150] Test steps:
[0151] S1. Sample preparation: Samples of coating materials from Examples 1, 2, 3, 4, and 5 are taken in a size of 10 cm × 10 cm and placed in a test box after surface treatment;
[0152] S2. Ultraviolet radiation test: set the wavelength range of the ultraviolet lamp to 200-400nm, the radiation intensity to 0.7W / m², and continuously expose for 240 hours. Record the color change of the sample and use a spectrophotometer to measure the reflectivity change.
[0153] S3, temperature change test: the temperature cycle is set from -20°C to 70°C, the cycle time is changed every 48 hours, and a total of 30 cycles are performed. The appearance changes and surface cracks of the samples are observed and recorded;
[0154] S4. Humidity test: Set the humidity range to 30%-90% and maintain it for 72 hours. Record the changes of the samples and conduct a water immersion test. Soak the samples in water for 48 hours to observe whether there is any shedding or bubbling.
[0155] Results recorded:
[0156] Color change: record the degree of color change of the sample after UV exposure and quantify the change using the ΔE value (color difference indicator);
[0157] Cracks and peeling: Record the extent of cracks and peeling through visual inspection and surface profile scanning;
[0158] Adhesion change: Use tape peel test to evaluate the adhesion of the coating after humidity changes;
[0159] Table 3- Weathering resistance test results
[0160] Test items Example 1 Example 2 Example 3 Example 4 Example 5 UV radiation ΔE value 2.5 3.0 1.8 2.9 2.2 Number of cracks 1 2 0 1 1 Stripping area 5% 10% 3% 6% 4% Humidity Effect No significant changes Slight bubbling on the surface No significant changes No significant changes Slight bubbling on the surface Temperature Cycling No cracks A few cracks No cracks No cracks A few cracks
[0161] Result analysis:
[0162] Ultraviolet radiation ΔE value: The ΔE values of all examples are within the acceptable range, and Example 3 performs best, showing excellent photochromic stability;
[0163] Number of cracks: No cracks were found in Example 3, indicating that it has superior performance in weather resistance and is suitable for long-term exposure to outdoor environments;
[0164] Peeling area: Although the peeling area of Example 2 is larger, the overall adhesion remains good in other examples, showing the reliability of the material;
[0165] Humidity effect: Examples 1, 3 and 4 were stable under high humidity conditions without significant changes, showing excellent moisture resistance;
[0166] Temperature Cycling: Overall performance is excellent, with a few cracks having little impact on functionality, proving that these materials can withstand temperature fluctuations.
[0167] In summary, all examples exhibit good weather resistance, especially Example 3, which is suitable for optical applications requiring high durability.
[0168] Anti-UV performance test example:
[0169] Purpose of the test: To evaluate the stability and durability of coating materials of different embodiments under ultraviolet (UV) radiation to determine their suitability and reliability in optical applications;
[0170] Test Method
[0171] Sample preparation: Samples were taken from each of Examples 1, 2, 3, 4, and 5 to prepare coatings of standard thickness;
[0172] UV radiation source: Use UV lamp (wavelength 254nm) for radiation testing to simulate the UV component in sunlight;
[0173] Radiation intensity: Set the radiation intensity to 100mW / cm²;
[0174] Test time: Radiation test is conducted at 24 hours, 48 hours, 72 hours and 96 hours respectively;
[0175] Test steps:
[0176] S1. Place the sample under the UV radiation source, ensuring that the distance from the light source is consistent;
[0177] S2. Record the appearance changes of the samples every 24 hours, including color changes, surface integrity and any cracks;
[0178] S3. Use a spectrophotometer to measure the transmittance change of the sample and record the UV transmittance;
[0179] Table 4 - UV resistance test results
[0180] Example Radiation time (hours) ΔE value Transmittance change (%) Number of cracks Surface integrity Example 1 24 1.5 10 0 intact Example 1 48 2.0 15 0 intact Example 1 72 3.0 20 1 Minor injuries Example 1 96 4.5 25 2 Obvious damage Example 2 24 1.2 8 0 intact Example 2 48 1.8 12 0 intact Example 2 72 2.8 18 1 Minor injuries Example 2 96 4.0 22 1 Minor injuries Example 3 24 0.8 5 0 intact Example 3 48 1.0 7 0 intact Example 3 72 1.5 10 0 intact Example 3 96 2.0 15 0 intact Example 4 24 1.5 11 0 intact Example 4 48 2.1 16 0 intact Example 4 72 3.2 21 1 Minor injuries Example 4 96 4.2 24 2 Obvious damage Example 5 24 1.3 9 0 intact Example 5 48 1.9 13 0 intact Example 5 72 2.6 17 1 Minor injuries Example 5 96 4.1 23 2 Obvious damage
[0181] Results Analysis
[0182] ΔE value: The ΔE values of all examples increased with the increase of irradiation time, and Example 3 performed best with the smallest ΔE value, indicating that it has high stability under UV irradiation;
[0183] Transmittance change: Example 3 has the smallest transmittance change, indicating that it has excellent UV resistance and is suitable for high-transparency optical coatings;
[0184] Number of cracks and surface integrity: Example 3 had no cracks during the entire test, while other examples showed slight damage over time. Example 3 showed excellent durability;
[0185] In summary, the UV resistance of Example 3 is the most outstanding and is suitable for applications exposed to light for a long time.
[0186] The technical features of the above embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0187] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A multi-tone ultraviolet photochromic coating material, characterized in that: The percentage by mass includes: 30-60% organic photochromic agent: composed of benzopyran compounds, including 3,4-dihydro-2H-1-benzopyran and 2H-benzopyran-2-one; 3,4-Dihydro-2H-1-benzopyran accounts for 40% of the total organic photochromic agents, and 2H-benzopyran-2-one accounts for 60% of the organic photochromic agents; Inorganic photochromic agent 20-50%: composed of nano-sized titanium oxide particles; Polymer matrix 10-30%: a combination of one or more of polyurethane, acrylic or epoxy resin; Additives 0.1-5%.
2. A multi-tone ultraviolet photochromic coating material according to claim 1, characterized in that: The auxiliary agent includes antioxidant, ultraviolet absorber and dispersant by mass percentage.
3. The multi-tone ultraviolet photochromic coating material according to claim 1, characterized in that: The organic photochromic agent further comprises a functional additive, and the functional additive is selected from a light stabilizer, a tackifier or an antibacterial agent.
4. A synthesis process of a multi-tone ultraviolet photochromic coating material according to any one of claims 1 to 3, characterized in that: The synthesis steps include: Step 1: Prepare raw materials; Step 2: In a stirrer, mix the required proportion of the organic photochromic agent and the polymer substrate, set the stirring speed to 300-500 rpm, and continue for 30 minutes to make the preliminary mixture uniform, then gradually add the nano-sized titanium oxide particles and continue stirring. The total stirring time reaches 60 minutes. After adding the auxiliary agent, continue stirring until the total time of the entire stirring process reaches 90 minutes; Step 3: After fully mixing, gradually add solvent as needed to make the viscosity of the mixture reach 500-1000cP for spraying. After stirring evenly, let it stand for 10 minutes to observe the bubbles in the mixture to ensure that there are no obvious bubbles. Step 4: Spray the coating material evenly on the surface to be treated. The coating thickness needs to be controlled at 50-100 microns, the ambient temperature is maintained at 20-25°C, and the humidity is controlled at 30-50%; Step 5: After coating, place the coating in a well-ventilated dry environment to dry naturally for 24 hours. Then, place the coating material in an oven preheated to 60-80°C for curing, and the curing time is set to 1-2 hours. Step 6: Perform photochromic performance, adhesion test, weather resistance test and UV resistance test on the cured coating.
5. A synthesis process of a multi-tone ultraviolet photochromic coating material according to claim 4, characterized in that: In the step 3, the gradually added solvent includes alcohols and ketones; The alcohol solvent is isopropanol or ethanol; Acetone is selected as the ketone solvent; Adding solvent is used to adjust the viscosity of the coating material. According to the required viscosity and formula, add the solvent gradually and stir well.
6. A synthesis process of a multi-tone ultraviolet photochromic coating material according to claim 4, characterized in that: In the step 4, the coating material is placed in a vacuum environment for degassing treatment, the vacuum degree is -0.1 to -0.2 MPa, and the treatment time is 10-20 minutes to remove bubbles generated during the mixing process.
Citation Information
Patent Citations
Photochromic plate and manufacturing process thereof
CN110615904A
Stabilized photochromic materials
US4166043A